Effect of Hepatitis B Virus (HBV) Infection on Lipid Profile in Ghanaian Patients. Issue 1 (February 2019) - Quaye, Osbourne; Amuzu, Benjamin Godfried; Adadey, Samuel Mawuli; Tagoe, Emmanuel Ayitey
Background: Worldwide, approximately 257 million people have chronic hepatitis B virus (HBV) infection, with the highest infection rates recorded in Africa and Asia. Although HBV infection has been associated with dyslipidemia, which may lead to death via liver related complications, the effect of the virus on the lipid profile of patients remain unclear. This study was designed to evaluate the effect of chronic hepatitis B virus infection on lipid profile of sero-positive individuals from Ghana. Methods: Blood samples were collected from chronic HBV infected patients who were recruited from the Korle-Bu Teaching Hospital, Accra, and HBV sero-negative healthy volunteers who were used as controls. Demographic and clinical data were obtained using a structured questionnaire. Blood pressure and body mass index were determined, and HBV profile markers and lipid profiles of the patients were determined using a commercially available kit and a chemistry analyzer, respectively. Results: Triglycerides, low density lipoproteins (LDL), high density lipoproteins (HDL), very low density lipoproteins (VLDL), and total cholesterol were used as indices of lipid metabolism disorder. Body mass index and diastolic blood pressures were significantly elevated in patients compared to healthy volunteers. Conclusion: The observed high total cholesterol and LDL, with a significantly lower HDL levels compared to healthy controls suggest an increased cardiovascular disease risk index in the patients. There is therefore the need to regularly monitor HBV infected patients for signs of cardiovascular diseases.